2007
DOI: 10.1681/asn.2006040407
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Are the Major Targets in Albumin-Induced Apoptosis in Proximal Tubule Cells

Abstract: Nephrotic-range proteinuria is considered a poor prognostic factor. A correlation between tubulointerstitial injury and the degree of proteinuria is well established. In an attempt to explain the tubular atrophy that is observed in advanced glomerulonephritides, this study investigated apoptotic mechanisms in cultured human proximal tubule cells (HKC-8) that were exposed to endotoxin-free albumin (5, 10, and 20 mg/ml). Apoptosis was detected by Hoechst 33342; annexin staining; and assays for caspases 3, 8, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 39 publications
4
56
0
1
Order By: Relevance
“…As shown in Supplemental Figure 2, transient transfection of Bcl-2 into RPTC suppressed albumin-induced cytochrome c release and apoptosis, whereas vector transfection was ineffective. Together, the results support the recent work by Erkan et al 7 that the mitochondrial pathway of apoptosis plays an important role in albumin-induced apoptosis in renal tubular cells.…”
Section: Effects Of Bcl-2 Expression On Albumin-induced Cytochrome C supporting
confidence: 91%
See 3 more Smart Citations
“…As shown in Supplemental Figure 2, transient transfection of Bcl-2 into RPTC suppressed albumin-induced cytochrome c release and apoptosis, whereas vector transfection was ineffective. Together, the results support the recent work by Erkan et al 7 that the mitochondrial pathway of apoptosis plays an important role in albumin-induced apoptosis in renal tubular cells.…”
Section: Effects Of Bcl-2 Expression On Albumin-induced Cytochrome C supporting
confidence: 91%
“…Erkan and colleagues 7 have recently demonstrated a role for the mitochondrial/intrinsic pathway of apoptosis in albumininduced apoptosis in HKC-8 renal tubular cells. Consistently, we showed cytochrome c release from mitochondria during albumin incubation of RPTC, which was suppressed by Bcl-2 expression (Figure 2).…”
Section: Effects Of Rottlerin On Albumin-induced Bax Translocation Anmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Thus, it was possible that the tubular proliferation occurred in response to albuminuria-induced apoptosis and reduced tubular cell numbers. However, terminal deoxynucleotidyl transferase-mediated digoxigenin-deoxyuridine nick-end labeling staining at 3, 5, and 7 days after podocyte ablation with 25 ng DT revealed that there was no increase in tubular cell apoptotic rates on days 3 and 5 (i.e., preceding the proliferation observed on days 6-7) and only a modest increase in apoptotic rates on day 7 (Figure 4, D and E).…”
Section: Podocyte Damage Stimulates Proliferation Of Proximal Tubularmentioning
confidence: 99%